2019
DOI: 10.17129/botsci.2135
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of efficient adventitious shoots induction system and ex vitro rooting in Vaccinium corymbosum (Ericaceae)

Abstract: <p align="left"><strong>Background</strong>: The extension of the blueberry industry in China is restricted by the low performance of proliferation coefficient, transplanting survival rate and the long cycle production.</p><p align="left"><strong>Hypothesis</strong>: We hypothesized the suitable medium with optimal concentration and type combination would improve the survival rate of <em>Vaccinium corymbosum.</em></p><p align="left"><strong&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…On the other hand, leaves and stems of regenerated shoots in the control treatment (without AgNPs) had a yellowish-reddish coloration, an indicator of nutritional deficiency. The development of yellowish or reddish shoots was also reported by Wang et al [12] and Li et al [32], being a characteristic response of shoots grown in WPM due to its low nutrient concentration, particularly nitrogen. Nonetheless, the addition of AgNPs showed a possible hormetic effect on the shoots, as the vitroplants slightly improved their coloring.…”
Section: Micropropagation Phasesupporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, leaves and stems of regenerated shoots in the control treatment (without AgNPs) had a yellowish-reddish coloration, an indicator of nutritional deficiency. The development of yellowish or reddish shoots was also reported by Wang et al [12] and Li et al [32], being a characteristic response of shoots grown in WPM due to its low nutrient concentration, particularly nitrogen. Nonetheless, the addition of AgNPs showed a possible hormetic effect on the shoots, as the vitroplants slightly improved their coloring.…”
Section: Micropropagation Phasesupporting
confidence: 71%
“…For the initiation of in vitro propagation, the sterilization of plant material is of crucial importance, especially when the explants come from the field [9]. On the other hand, during the multiplication stage, different growth regulators are usually used to induce the development of new shoots [10][11][12]. However, in recent years, the addition of nanomaterials has been shown to be a revolutionary alternative to optimize organogenesis protocols [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 27 reported that NAA has a weak in uence on buds, which suggested a signi cant role of optimal KT in increasing the proliferation rate. However, with increasing cytokinin concentrations negatively affected the shoot regeneration frequency, which was consistent with Rejthar et al 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Plant tissue culture has been widely used in plant breeding, which has clearly advantages in maintaining clonal genetic characteristics, shortening the breeding cycle, improving reproductive efficiency and economic benefits (Wang et al 2019). Compared with the five stages for traditional tissue culture, including aseptic system establishment, primary culture, subculture and rapid propagation, rooting induction, and acclimatization, one-step culture is simpler and more efficient, and can avoid the germplasm variation (Loyola-Vargas and Ochoa-Alejo 2018).…”
Section: Establishment Of One-step Culture For Tetraploid Plantletmentioning
confidence: 99%